A framework for assessing alternate proliferation pathways in the age of non-state actors. Issue 1 (2nd January 2018) - Bevins, James E.; Laderman, Sarah; Goldblum, Bethany L.; Katzenson, Elie; Kendrick, James; Krentz-Wee, Rebecca; Tian, Yubing
Abstract : While the nonproliferation community has long acknowledged the possibility of nuclear terrorism, its prevention has become a central focus area in recent years. For decades it has been assumed that, with access to special nuclear material (SNM), the steps to indigenously develop an improvised nuclear device are within the reach of non-state actors. At the same time, indigenous production of SNM has generally been dismissed as infeasible. Recognizing how recent trends of technology democratization, the open exchange of information, and globalization have eroded certain barriers to proliferation by non-state actors, this research explores the pathways a non-state actor could take to indigenously develop SNM and develops a method to determine the comparative attractiveness of each pathway, given the current capabilities of non-state actors. Additionally, it considers avenues for further investigation to identify countermeasures for SNM production, including countermeasures specific to non-state actors.